1992
DOI: 10.1161/01.str.23.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of transcranial Doppler and cerebral blood flow studies to assess cerebral vasoreactivity.

Abstract: Background and Purpose: The aim of this study was to determine the ability of transcranial Doppler ultrasonography when used to assess cerebral vasoreactivity. The results of this method were compared with regional cerebral blood flow measurements.Methods: Forty-three patients with symptoms suggesting cerebrovascular disease took part Transcranial Doppler findings in the middle cerebral arteries were compared with regional cerebral blood flow in the corresponding perfusion territories before and after acetazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
98
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(108 citation statements)
references
References 16 publications
9
98
0
1
Order By: Relevance
“…Transcranial Doppler sonography is an easily available tool wherein CVR is represented by the percentage of mean velocity increase after administration of vasodilatory stimuli. 25 However, transcranial Doppler sonography is also highly technique-dependent and cannot be applied in patients with a poor temporal window. Moreover, critical carotid stenosis may result in the absence of any MCA signal intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial Doppler sonography is an easily available tool wherein CVR is represented by the percentage of mean velocity increase after administration of vasodilatory stimuli. 25 However, transcranial Doppler sonography is also highly technique-dependent and cannot be applied in patients with a poor temporal window. Moreover, critical carotid stenosis may result in the absence of any MCA signal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] However, there are very few published reports on the evaluation of CVR by functional MR imaging (fMRI). 29,30 Blood oxygen leveldependent (BOLD) signal-intensity activation revealed by fMRI is sensitive during increased cerebral blood flow (CBF) and is often used for detecting the changes in cerebral perfu-sion under various physiologic conditions.…”
mentioning
confidence: 99%
“…Other factors may also explain this discrepancy, e.g., a hand-held 2-MHz probe. 8,27 Fixation is particularly important when relative changes in CBF during different procedures are investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the diameter of the MCA remains constant during anesthesia 23,24 and that changes in Vmca accurately reflect changes in cerebral blood flow. [25][26][27][28] Standard measures for CBF correlate well with CBFV data obtained by TCD in both adults and neonates. [28][29][30] The insonating angle, i.e., the angle between the ultrasonic beam and the insonated vessel axis, was kept constant throughout the study by using a custom made wheel to fix the TCD probe to the patient's head.…”
mentioning
confidence: 55%